A Total systems study on the Production Monitoring System of Benguet Management Corporation (Plant 1, Foundry Division) - Mendoza, Ma. Eleanor P.; Olegario, Audrey D.; Pascual, Lourdes Kathleen M.; Pulido, Ma. Rowena Guadalupe P.; Tiu, Daniel Y. (College of Engineering, 1993)
This study is centered on Plant 1 of Benguet Management Corporation. Plant 1 includes these sections, namely: the Pattern Making Section, the Core/Molding Section, and the Melting Section. Based on conducet interviews and numerous observations in the shop floor, the group has formulated several findings on the present system of the company. Below are the different findings along with the group's recommendations. FINDINGS: Pattern Making Section, Raw materials used are not recorded per pattern made, Man hours spent on processing a pattern cannot be determined, Core/Molding Section, There is no record of adjustments or changes in the ratios of raw materials, Raw materials used are not recorded effectively, Man hours spent on processing a mold/core cannot be determined, Quality tests results are not recorded, Loose documentation in the shop floor, No inventory of work-in-process (WIP) for Core Section, No properly authorized/validated transfer of product items to Shake Out/ Heat Treatment Section, No proper identification of order/castings, Melting Section, There is consumption of raw materials even when there is no withdrawal of it, Errors in filling up of forms due to small spacings in the forms. RECOMMENDATIONS: Redesigning of the Pattern Making/Repair Record, Redesigning of the Pattern Making/Repair Record, Use of the Route Sheet for the Molding Section, Use of the Molding Section Route Sheet, Use of the Molding Section Route Sheet, Use of Quality Reports, Use of the Route Sheet and Traveller's card, Use of the Status Report, Employment of Endorsement Slip, Making use of the Traveller's card, Use of the Molding Section Route Sheet, Use of the Molding Section Route Sheet.